Evaluation of Nanomagnetite–Biochar Composite for BTA Removal - Carolina Guida; Nathaniel Findling; Valérie Magnin; Fabienne Favre Boivin; Laurent Charlet (Nanomaterials)
In this study, the removal of benzotriazole (BTA), a pervasive aquatic contaminant widely used for its anti-corrosion, UV-stabilizing, and antioxidant properties, by nanomagnetite, biochar, and nanomagnetite–biochar composite is investigated. Nanomagnetite and nanomagnetite–biochar composite were synthesized under anoxic conditions and tested for BTA removal efficiency at neutral pH under both oxic and anoxic conditions at different time scales. Within the short time scale (up to 8 h), the removal of BTA by nanomagnetite–biochar composite was shown to be due to BTA deprotonation by the nanomagnetite surface. Through proton liberation, Fe²⁺ is released in accordance with the reaction Fe₃O₄ + 2H⁺ → Fe₂O₃ + Fe²⁺ + H₂O, which likely influences BTA complexation and its possible redox degradation. On the longer time scale, biochar achieved higher removal efficiency: 50% BTA removed within 48 h, due to formation of a ternary complex with surface Ca2+ ions, or 75% BTA removed after HCl biochar acid wash followed by Ca2+ surface saturation. As BTA presents significant environmental risks due to its extensive industrial applications, the present study offers critical insights into the mechanisms of BTA removal by nanomagnetite–biochar composite, and highlights the potential of such materials for water treatment applications.